Une lecture biographique de la poésie de Xu Lizhi - Beaton GALAFA (Altralang Journal, 2023)
ABSTRACT: This article undertakes a biographical reading of the poetry of Xu Lizhi, a Chinese migrant worker who committed suicide in 2014. It analyses his poems published posthumously in the 2015 anthology “La machine est ton seigneur et ton maître”. The article interrogates the poetry through three specific objectives: (1) to explore the representation of the poet’s despair and distress as an immigrant worker; (2) to explore the concept of death before actual death, as experienced in a life of suffering; and (3) to explore the motif of suicide as prophecy. Thus, the poet’s lived experiences offer insights into the psychic state that underlies the literary ingenuity expressed in his poems.